Sosialisasi Kewirausahaan pada UMKM Ecoprint KWT Pandan Arum Kjang untuk Meningkatkan Usaha Ekonomi Kreatif di Kelurahan Pajang - Fatihah, Dea Luthfiana; Hardiyanti, Tia; Kristanti, Kharisma; Pratama, Raditya Yoga; Yulfika, Alif Satria; Nugrahadi, Bekti (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Ecoprint KWT Pandan Arum 48 Kjang is one of the entrepreneurial potentials that exists in Kelurahan Pajang. This effort was created at the same time as the Climate Village Race (PROKLIM). But the awareness of this effort and the marketing strategy used is still not optimal, because only through mouth-to-mouth and WhatsApp. Therefore, we strive to provide understanding related to product innovation, waste treatment, as well as the use of digital technology in the world of business, that is, digital marketing. The purpose of the submission is to improve skills, learn how to manage waste properly, and reach a broader market for the entrepreneur Ecoprint KWT Pandan Arum 48 Kjang. We realize these activities through the socialization of entrepreneurship. Thus, through this socialization, it is expected to increase competitiveness, expand the reach of the market, and make Ecoprint KWT Pandan Arum Pajang a sustainable business.